Aufgabengenerator: Quadratische Funktion


 Nr.
 Polynomform
 Scheitelpunktform
 Linearfaktoren
 Schnittpunkte
 Scheitelpunkt
x-Achse
y-Achse
 1.)
 f(x) = 3 x2 + 9 x + 6
 f(x) = 3 (x + 1.5)2 - 0.75
 f(x) = 3 (x + 2) (x + 1)
 x1 = -2
 x2 = -1
 y = 6
 SP = (-1.5 / -0.75 )
 2.)
 f(x) = 2 x2 - 26 x + 84
 f(x) = 2 (x - 6.5)2 - 0.5
 f(x) = 2 (x - 6) (x - 7)
 x1 = 6
 x2 = 7
 y = 84
 SP = (6.5 / -0.5 )
 3.)
 f(x) = -1 x2 + 5 x + 6
 f(x) = -1 (x - 2.5)2 + 12.25
 f(x) = -1 (x + 1) (x - 6)
 x1 = -1
 x2 = 6
 y = 6
 SP = (2.5 / 12.25 )
 4.)
 f(x) = -0.25 x2 + 3 x - 8.75
 f(x) = -0.25 (x - 6)2 + 0.25
 f(x) = -0.25 (x - 5) (x - 7)
 x1 = 5
 x2 = 7
 y = -8.75
 SP = (6 / 0.25 )
 5.)
 f(x) = -0.5 x2 - 0.5 x
 f(x) = -0.5 (x + 0.5)2 + 0.125
 f(x) = -0.5 x (x + 1)
 x1 = 0
 x2 = -1
 y = 0
 SP = (-0.5 / 0.125 )
 6.)
 f(x) = 1 x2 - 6 x + 5
 f(x) = 1 (x - 3)2 - 4
 f(x) = 1 (x - 5) (x - 1)
 x1 = 5
 x2 = 1
 y = 5
 SP = (3 / -4 )
 7.)
 f(x) = 1 x2 - 25
 f(x) = 1 x2 - 25
 f(x) = 1 (x + 5) (x - 5)
 x1 = -5
 x2 = 5
 y = -25
 SP = (-0 / -25 )
 8.)
 f(x) = 0.75 x2 - 9 x + 26.25
 f(x) = 0.75 (x - 6)2 - 0.75
 f(x) = 0.75 (x - 7) (x - 5)
 x1 = 7
 x2 = 5
 y = 26.25
 SP = (6 / -0.75 )
 9.)
 f(x) = -0.667 x2 - 7.333 x - 18.667
 f(x) = -0.667 (x + 5.5)2 + 1.5
 f(x) = -0.667 (x + 4) (x + 7)
 x1 = -4
 x2 = -7
 y = -18.667
 SP = (-5.5 / 1.5 )
 10.)
 f(x) = 1 x2 + 3 x - 18
 f(x) = 1 (x + 1.5)2 - 20.25
 f(x) = 1 (x - 3) (x + 6)
 x1 = 3
 x2 = -6
 y = -18
 SP = (-1.5 / -20.25 )
 11.)
 f(x) = 0.25 x2 - 2.25 x + 5
 f(x) = 0.25 (x - 4.5)2 - 0.063
 f(x) = 0.25 (x - 4) (x - 5)
 x1 = 4
 x2 = 5
 y = 5
 SP = (4.5 / -0.063 )
 12.)
 f(x) = -2 x2 + 98
 f(x) = -2 x2 + 98
 f(x) = -2 (x + 7) (x - 7)
 x1 = -7
 x2 = 7
 y = 98
 SP = (-0 / 98 )
 13.)
 f(x) = 0.667 x2 + 2 x - 2.667
 f(x) = 0.667 (x + 1.5)2 - 4.167
 f(x) = 0.667 (x - 1) (x + 4)
 x1 = 1
 x2 = -4
 y = -2.667
 SP = (-1.5 / -4.167 )
 14.)
 f(x) = 0.333 x2 + 2.333 x
 f(x) = 0.333 (x + 3.5)2 - 4.083
 f(x) = 0.333 (x + 7) x
 x1 = -7
 x2 = -0
 y = 0
 SP = (-3.5 / -4.083 )
 15.)
 f(x) = -0.25 x2 - 1.25 x - 1
 f(x) = -0.25 (x + 2.5)2 + 0.563
 f(x) = -0.25 (x + 4) (x + 1)
 x1 = -4
 x2 = -1
 y = -1
 SP = (-2.5 / 0.563 )
 16.)
 f(x) = -2 x2 - 6 x - 4
 f(x) = -2 (x + 1.5)2 + 0.5
 f(x) = -2 (x + 2) (x + 1)
 x1 = -2
 x2 = -1
 y = -4
 SP = (-1.5 / 0.5 )
 17.)
 f(x) = -2 x2 + 8 x + 42
 f(x) = -2 (x - 2)2 + 50
 f(x) = -2 (x + 3) (x - 7)
 x1 = -3
 x2 = 7
 y = 42
 SP = (2 / 50 )
 18.)
 f(x) = 0.5 x2 + 2 x - 10.5
 f(x) = 0.5 (x + 2)2 - 12.5
 f(x) = 0.5 (x - 3) (x + 7)
 x1 = 3
 x2 = -7
 y = -10.5
 SP = (-2 / -12.5 )
 19.)
 f(x) = -0.5 x2 - 0.5 x + 21
 f(x) = -0.5 (x + 0.5)2 + 21.125
 f(x) = -0.5 (x + 7) (x - 6)
 x1 = -7
 x2 = 6
 y = 21
 SP = (-0.5 / 21.125 )
 20.)
 f(x) = -2 x2 + 26 x - 84
 f(x) = -2 (x - 6.5)2 + 0.5
 f(x) = -2 (x - 6) (x - 7)
 x1 = 6
 x2 = 7
 y = -84
 SP = (6.5 / 0.5 )
 21.)
 f(x) = -0.25 x2 + 3.25 x - 10.5
 f(x) = -0.25 (x - 6.5)2 + 0.063
 f(x) = -0.25 (x - 6) (x - 7)
 x1 = 6
 x2 = 7
 y = -10.5
 SP = (6.5 / 0.063 )
 22.)
 f(x) = -0.333 x2 - 1.667 x + 4.667
 f(x) = -0.333 (x + 2.5)2 + 6.75
 f(x) = -0.333 (x + 7) (x - 2)
 x1 = -7
 x2 = 2
 y = 4.667
 SP = (-2.5 / 6.75 )
 23.)
 f(x) = 3 x2 + 15 x - 18
 f(x) = 3 (x + 2.5)2 - 36.75
 f(x) = 3 (x - 1) (x + 6)
 x1 = 1
 x2 = -6
 y = -18
 SP = (-2.5 / -36.75 )
 24.)
 f(x) = -2 x2 - 12 x
 f(x) = -2 (x + 3)2 + 18
 f(x) = -2 x (x + 6)
 x1 = -0
 x2 = -6
 y = -0
 SP = (-3 / 18 )
 25.)
 f(x) = 0.25 x2 + 0.25 x - 7.5
 f(x) = 0.25 (x + 0.5)2 - 7.563
 f(x) = 0.25 (x + 6) (x - 5)
 x1 = -6
 x2 = 5
 y = -7.5
 SP = (-0.5 / -7.563 )
 26.)
 f(x) = 0.5 x2 + 4 x + 3.5
 f(x) = 0.5 (x + 4)2 - 4.5
 f(x) = 0.5 (x + 1) (x + 7)
 x1 = -1
 x2 = -7
 y = 3.5
 SP = (-4 / -4.5 )
 27.)
 f(x) = 0.5 x2 - 0.5 x - 1
 f(x) = 0.5 (x - 0.5)2 - 1.125
 f(x) = 0.5 (x - 2) (x + 1)
 x1 = 2
 x2 = -1
 y = -1
 SP = (0.5 / -1.125 )
 28.)
 f(x) = -0.333 x2 + 0.333
 f(x) = -0.333 x2 + 0.333
 f(x) = -0.333 (x + 1) (x - 1)
 x1 = -1
 x2 = 1
 y = 0.333
 SP = (-0 / 0.333 )
 29.)
 f(x) = 1 x2 + 8 x + 12
 f(x) = 1 (x + 4)2 - 4
 f(x) = 1 (x + 2) (x + 6)
 x1 = -2
 x2 = -6
 y = 12
 SP = (-4 / -4 )
 30.)
 f(x) = -0.667 x2 - 2.667 x
 f(x) = -0.667 (x + 2)2 + 2.667
 f(x) = -0.667 x (x + 4)
 x1 = -0
 x2 = -4
 y = -0
 SP = (-2 / 2.667 )